Simulation Design of a Photovoltaic-based Reliable Street Lighting System using PVSyst Software - Khan, Muhammad Muneeb; Ahmad, Sadiq; Sikandar, Haroon; Akram, Basit; Hussain, Mushtaq; Anjum, Zeshan Haider (2024 International Conference on Emerging Trends in Smart Technologies (ICETST), 2024)
As conventional fossil fuels run out and their environmental effects worsen, renewable energy sources like photovoltaic (PV) energy are becoming more and more popular as clean, sustainable electricity sources, and shortage of power in Pakistan and excess load shedding is increasing day by day. The kind of photovoltaic modules, the potential for solar radiation, and the location all affect how well photovoltaic systems work. This study, a standalone solar PV system that powers a clean and green energy-efficient street lighting system is designed and simulated using PVsyst simulation software. The simulation is run to examine the standalone PV system's monthly/annual energy generation (kWh) and output power for street lights in the Institute of Southern Punjab Multan. Additionally, the system has various battery and solar losses. For the standalone PV system, three parallel strings with two series-connected Solar model PV-TE120MF5N of 120 Wp solar cell modules are utilized. To power the system throughout the night, a total of 12 lead acid tubular batteries with a voltage of 24 volts and a capacity of 3450 Ah are needed. These batteries are part of the OPzS solar 4600 battery type. According to the modeling findings, the yearly output of specific energy and total available energy was determined to be 1306 kWh/kWp and 940.6 kWh respectively. Battery aging depends on the state of wear which depends on the cycle and static state, according to the simulation proposed battery wear on the cycle is 99.1%, and in the static state 80.0% and the battery lifetime is 5 years. Performance ratio (PR) data shows that the greatest PR for the proposed PV system was 73.5% in January, the lowest PR for the system was 43.8% in September, and the average PR for the system over the course of a year was 54.7%. Following the identification of the primary cause of energy losses, the loss diagrams computed and displayed the specific losses for the entire year. The suggested system's cost-effectiveness was assessed using a straightforward payback time computation.